Metatranscriptome Profiling Indicates Size-Dependent Differentiation in Plastic and Conserved Community Traits and Functional Diversification in Dinoflagellate Communities - Wohlrab, Sylke; Falcke, Jan M.; Lin, Senjie; Zhang, Huan; Neuhaus, Stefan; Elferink, Stephanie; Voss, Daniela; Zielinski, Oliver; John, Uwe (Frontiers in Marine Science, 2018)
Communities of microscopic dinoflagellates are omnipresent in aquatic ecosystems. Consequently, their traits drive community processes with profound effects on global biogeochemistry. Species traits are however not necessarily static but respond to environmental changes in order to maintain fitness and may differ with cell size that scales physiological rates. Comprehending such trait characteristics is necessary for a mechanistic understanding of plankton community dynamics and resulting biogeochemical impacts. Here we used information theory to analyze metatranscriptomes of micro- and nano-dinoflagellate communities in three ecosystems. Measures of gene expression variations were set as a proxy to determine conserved and plastic community traits and the environmental influence on trait changes. Using metabarcoding, we further investigated if communities with a more similar taxon composition also express more similar traits. Our results indicate that plastic community traits mainly arise from membrane vesicle associated processes in all the environments we investigated. A specific environmental influence on trait plasticity was observed to arise from nitrogen availability in both size classes. Species interactions also appeared to be responsible for trait plasticity in the smaller-sized dinoflagellates. Additionally, the smaller-sized dinoflagellate communities are characterized by a large pool of habitat specific genes despite being taxonomically more similar across the habitats, in contrast to the microplanktonic assemblages that adapted to their environments by changing species composition. Our data highlight the functional diversification as a signature of smaller sized dinoflagellates, nitrogen availability and species interactions as drivers of trait plasticity, and traits most likely linked to fitness and community performance.